2002
DOI: 10.1001/archsurg.137.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Parathyroid Hormone Measurement in Patients With Secondary Hyperparathyroidism

Abstract: Secondary hyperparathyroidism decreases renal clearance of parathyroid hormone (PTH). Objective: To determine whether rapid PTH assays can be used to predict the success of a total parathyroidectomy to treat symptomatic secondary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 15 publications
6
66
0
Order By: Relevance
“…The quick intraoperative parathormone assay (qPTH) has proven its reliability and applicability as a predictor of successful surgical treatment of primary and secondary HPT (20,21). The qPTH can accurately facilitate unilateral, directed neck exploration for uniglandular PTG disease, as well as guide the extent of gland resection for multiglandular disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…The quick intraoperative parathormone assay (qPTH) has proven its reliability and applicability as a predictor of successful surgical treatment of primary and secondary HPT (20,21). The qPTH can accurately facilitate unilateral, directed neck exploration for uniglandular PTG disease, as well as guide the extent of gland resection for multiglandular disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…Cure rates of Ͼ95% have been reported in several studies (7,29,32,49,50 ), including one study with up to 5 years of follow-up (51 ). In addition, the rapid PTH assay has been shown to be useful in cases of secondary-tertiary hyperparathyroidism (32,39,52 ), as well as in reoperative cases for failed surgery or recurrent disease (32,45,53,54 ). The assay has also been reported to predict severe postoperative hypocalcemia in reoperative patients with multiglandular disease (55 ).…”
Section: Clinical Utility Of Rapid Intraoperative Pth Testsmentioning
confidence: 99%
“…This advantage does not always mean better patient outcomes, the medical unit that would like to perform POCT should be interested in the real impact of results in clinical practice, besides the accuracy of devices. Kendal et al [1] [13] 2000 Prospective USA 1788 NR Borgard [14] 2006 Prospective France 473 NR Engle [15] 2002 Prospective USA 404 NR Ho [16] 2006 Prospective China 4689 SN, SP, PPV, NPV Kazmierczak [17] 2004 Prospective USA Unclear NR Lam [18] 2008 Prospective China 113 SN, SP Maisels [19] 2004 Prospective USA 849 NR Mielsch [20] 2010 Prospective Germany 240 NR Robertson [21] 2002 Prospective USA 101 NR Rolinski [22] 2001 Prospective Germany 142 NR Rubaltelli [23] 2001 Prospective Italy NR NR Schmidt [24] 2009 Cohort USA 94 SN, SP, NPV Schumacher [25] 1995 Prospective USA NR NR Tan [26] 1996 Prospective Singapore 540 NR Tayaba [27] 1998 Prospective USA 900 NR Wong [28] 2002 Prospective UK 64 PPV Yamanouchi [29] 1980 Prospective Japan NR NR Yamauchi [30] 1988 Prospective Japan 576 NR Procalcitonin Bektas [31] 2011 Prospective Turkey 141 SN, SP, LR+, LRGaletto-Lacour [32] 2003 Prospective Switzerland 99 SN, SP, PPV, NPV Hesselink [33] 2009 Prospective Netherlands 101 NR Meisner [34] 2000 Prospective Germany 237 NR PTH Agarwal [35] 2001 Prospective Australia 88 NR Chou [36] 2002 Case series Taiwan NR NR Garner [37] 1999 Prospective NC 130 NR Johnson [38] 2001 Prospective USA 104 NR Mace [39] 2008 Prospective UK 20 NR Sokoll [40] 2000 Prospective USA 200 NR Troponin Apple [41] 2000 Prospective USA 1550 SN, SP Apple [42] 2006 Observational retrospective USA 545 NR Birkhahn [43] 2010 Prospective USA 151 SN, SP, PPV, NPV Bock [44] 2008 Prospective US...…”
Section: Discussionmentioning
confidence: 99%
“…Only one [38] out of six studies about PTH evaluated reduction on TAT and LOS. The study of Chou et al [36] reported numbers of re-interventions (two patients had a secondary operation) and surgery complications. The majority of studies considered 'important patient outcome' is in the Tn group: eight out of 25 studies (32%) evaluated reduction on LOS, of these seven considered also TAT.…”
Section: Patient Important Outcomesmentioning
confidence: 99%